Structural Basis for Env Incorporation into HIV-1 Particles - R. Elliot Murphy; Alexandra B. Samal; Gunnar Eastep; Ruba H. Ghanam; Peter E. Prevelige; Jamil S. Saad (Proceedings, 2020)
During the late phase of the HIV-1 replication cycle, the Gag polyproteins are transported to the plasma membrane (PM) for assembly. Gag targeting and assembly on the PM is dependent on interactions between its matrix (MA) domain and phosphatidylinositol-4,5-bisphosphate (PI(4,5)P2). Subsequent to Gag assembly, the envelope (Env) protein is recruited to the PM for incorporation into virus particles. Evidence suggests that the incorporation of the Env protein is mediated by interactions between the MA domain of Gag and the cytoplasmic tail of the gp41 subunit of Env (gp41CT), a mechanism that remains to be elucidated. Trimerization of the MA domain of Gag appears to be an obligatory step for this interaction. The interplay between gp41CT, the MA trimer, and the membrane has yet to be determined. Our lab has pioneered methods and approaches to investigate, at the molecular level, how the retroviral MA domains of Gag interact with membranes, a key requirement for understanding the Gag assembly and Env incorporation. Herein, we devised innovative approaches that will enable the structural characterization of the gp41CT–MA–membrane interactions. We employed structural biology (NMR and cryo-electron microscopy, biophysical methods, and biochemical tools to generate a macromolecular picture of how the MA domain of Gag binds to the membrane and how it interacts with gp41CT. To this end, we: (i) determined the three-dimensional structure of HIV-1 gp41CT and characterized its interaction with the membrane, (ii) engineered trimeric constructs of gp41CT and the MA to recapitulate the native and functional states of the proteins, and (iii) utilized membrane nanodisc technology to anchor the MA and gp41CT proteins. Our studies will allow for a detailed structural characterization of the gp41CT–MA–membrane interactions, which will advance our knowledge of HIV-1 Gag assembly and Env incorporation.